The Effect of Donor Age and Recipient Characteristics on Renal Outcomes in Patients Receiving Prolonged-Release Tacrolimus After Liver Transplantation: Post-Hoc Analyses of the DIAMOND Study - Trunečka, Pavel; Klempnauer, Jürgen; Bechstein, Wolf Otto; Pirenne, Jacques; Bennet, William; Zhao, Alexey; Isoniemi, Helena; Rostaing, Lionel; Settmacher, Utz; Mönch, Christian; Brown, Malcolm; Undre, Nasrullah; et al. (Annals of transplantation, 2019)
BACKGROUND The DIAMOND study of de novo liver transplant patients showed that prolonged-release tacrolimus exposure in the acute post-transplant period maintained renal function over 24 weeks of treatment. To assess these findings further, we performed a post-hoc analysis in patients according to baseline kidney function, Model for End-stage Liver Disease [MELD] scores, and donor age. MATERIAL AND METHODS Patients received prolonged-release tacrolimus (initial-dose, Arm 1: 0.2 mg/kg/day, Arm 2: 0.15-0.175 mg/kg/day, Arm 3: 0.2 mg/kg/day delayed until Day 5), mycophenolate mofetil and 1 steroid bolus. Arms 2 and 3 also received basiliximab. The recommended tacrolimus target trough levels to Day 42 post-transplantation were 5-15 ng/mL in all arms. In this post-hoc analysis, change in renal outcome, based on estimated glomerular filtration rate (eGFR), Modified Diet in Renal Disease-4 (MDRD4), values from baseline to Week 24 -post-transplantation, were assessed according to baseline patient factors: eGFR (≥60 and ˂60 mL/min/1.73 m²), MELD score (˂25 and ≥25) and donor age (˂50 and ≥50 years). RESULTS Baseline characteristics were comparable (Arms 1-3: n=283, n=287, n=274, respectively). Patients with baseline renal function, eGFR ≥60 mL/min/1.73 m², experienced a decrease in eGFR in all tacrolimus treatment arms. In patients with lower baseline renal function (eGFR ˂60 mL/min/1.73 m²), an advantage for renal function was observed with both the early lower-dose and delayed higher-dose tacrolimus regimens compared with the early introduction of higher-dose tacrolimus. At Week 24, renal function was higher in the early-lower tacrolimus arm with older donors, and the delayed higher-dose tacrolimus arm with younger donors, both compared with early higher-dose tacrolimus. CONCLUSIONS Pre-transplantation factors, such as renal function and donor age, could guide the choice of prolonged-release tacrolimus regimen following liver transplantation.
Keywords: transplantace jater; senioři; rejekce štěpu; Delayed-Action Preparations; Immunosuppressive Agents; Tissue Donors; dárci tkání; Mycophenolic Acid; Middle Aged; Tacrolimus; mužské pohlaví; kyselina mykofenolová; Adult; Kidney Function Tests; věkové faktory; léky s prodlouženým účinkem; takrolimus; ženské pohlaví; Graft Rejection; imunosupresiva; Humans; Transplant Recipients; příjemce transplantátu; Liver Transplantation; ledviny; lidé středního věku; vyšetření funkce ledvin; Age Factors; Kidney Failure, Chronic; dospělí; Kidney; chronické selhání ledvin; Female; Aged; lidé; Male